IMPACT OF MARKETING FLEXIBILITY ON THE MARKETING PERFORMANCE OF ENTREPRENEURIAL BUSINESS - Kyurova, Vyara (Revista Inclusiones, 2021)
To ensure not only their competitive advantages, but also their survival in the market, especially in the current pandemic environment, entrepreneurs are looking for new ways to ensure a lasting market presence, efficiency and growth, as well as opportunities to create a high degree of trust and customer loyalty. The application of the marketing flexibility approach by the representatives of the entrepreneurial business is a prerequisite for achieving lasting success in the marketing activity and timely response to the changing consumer interests and needs. In this regard, the main objective of this paper is to establish the relationship between marketing flexibility and marketing performance of the enterprise. This paper uses statistical methods (dispersion, regression and correlation analysis) to study the impact of marketing flexibility on the marketing performance of enterprises. A questionnaire was used as a method for collecting primary data. The evaluation of the studied indicators is carried out on a 7-point scale. The results of the study show a strong relationship between the degree of marketing flexibility and marketing performance of enterprises. In conclusion, generalized conclusions are made related to the use of marketing flexibility as an important tool for sustainable market presence and maintaining competitive advantage.